(untitled) (Clinics, 2016)
OBJECTIVE: To identify the main severe potential drug-drug interactions in older adults with dementia and to examine the factors associated with these interactions. METHOD: This was a cross-sectional study. The enrolled patients were selected from six geriatrics clinics of tertiary care hospitals across Mexico City. The patients had received a clinical diagnosis of dementia based on the current standards and were further divided into the following two groups: those with severe drug-drug interactions (contraindicated/severe) (n=64) and those with non-severe drug-drug interactions (moderate/minor/absent) (n=117). Additional socio-demographic, clinical and caregiver data were included. Potential drug-drug interactions were identified using Micromedex Drug Reax 2.0® database. RESULTS: A total of 181 patients were enrolled, including 57 men (31.5%) and 124 women (68.5%) with a mean age of 80.11±8.28 years. One hundred and seven (59.1%) patients in our population had potential drug-drug interactions, of which 64 (59.81%) were severe/contraindicated. The main severe potential drug-drug interactions were caused by the combinations citalopram/anti-platelet (11.6%), clopidogrel/omeprazole (6.1%), and clopidogrel/aspirin (5.5%). Depression, the use of a higher number of medications, dementia severity and caregiver burden were the most significant factors associated with severe potential drug-drug interactions. CONCLUSIONS: Older people with dementia experience many severe potential drug-drug interactions. Anti-depressants, antiplatelets, anti-psychotics and omeprazole were the drugs most commonly involved in these interactions. Despite their frequent use, anti-dementia drugs were not involved in severe potential drug-drug interactions. The number and type of medications taken, dementia severity and depression in patients in addition to caregiver burden should be considered to avoid possible drug interactions in this population.